2015
DOI: 10.1158/0008-5472.can-14-2061
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-Dependent Signaling Decreases the Antitumor Efficacy of Epidermal Growth Factor Receptor Inhibition in Head and Neck Cancer Cells

Abstract: Epidermal growth factor receptor (EGFR) is upregulated in the majority of head and neck squamous cell carcinomas (HNSCC). However many HNSCC patients respond poorly to the EGFR inhibitors (EGFRIs) cetuximab and erlotinib despite tumor expression of EGFR. Gene expression analysis of erlotinib-treated HNSCC cells revealed an upregulation of genes involved in MyD88-dependent signaling compared to their respective vehicle-treated cell lines. We therefore investigated if MyD88-dependent signaling may reduce the ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Interestingly, a recent publication emphasized the importance of IL1R-dependent signaling in HNSCCs. Therein, signaling from the IRAK1 adapter protein MyD88 was increased in response to erlotinib treatment in EGFR-amplified HNSCCs [ 22 ]. Furthermore, inhibition of IL1R signaling enhanced sensitivity to erlotinib treatment, thus supporting clinical potential for the targeting of TLR/IL1R signaling pathways in these cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent publication emphasized the importance of IL1R-dependent signaling in HNSCCs. Therein, signaling from the IRAK1 adapter protein MyD88 was increased in response to erlotinib treatment in EGFR-amplified HNSCCs [ 22 ]. Furthermore, inhibition of IL1R signaling enhanced sensitivity to erlotinib treatment, thus supporting clinical potential for the targeting of TLR/IL1R signaling pathways in these cancers.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that erlotinib treatment activated the IL-1 pathway in HNSCC cells which limited the efficacy of erlotinib in HNSCC cells [16]. The IL-1 pathway plays a central role in inflammatory responses by regulating the expression of various inflammatory genes in immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…The functional analysis suggested an activation of inflammatory pathways that might be mediated by MyD88. Further experiments suggested the IL-1α/IL-1R/MYD88/IL-6 pathway as responsible for the reduced anti-tumor efficacy of erlotinib and other EGFR inhibitors [ 23 ]. However, in HNSCC cells these processes were upregulated, whereas in our experiments after 24 h treatment most genes involved in these pathways were downregulated.…”
Section: Discussionmentioning
confidence: 99%